Designing Model of Business English Material Using Communicative Approach - Santoso, Andi; Sanjaya, Ricky Eka (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
This paper tries to provide a simple and communicative model of business English materials that can be applied in the classroom. In this regard, the language skill taught is speaking with the targeted micro-skills of business vocabulary and function-based language focus (grammar). A communicative approach is used in the development of the materials in order to facilitate the learners to use the language in various social contexts with interlocutors. Accordingly, the method of instruction is a role-play.